2014
DOI: 10.1007/s10661-014-3882-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative research on NIMBY risk acceptability between Chinese and Japanese college students

Abstract: Along with the progressive acceleration of urbanization, the need to identify potentially troublesome "Not In My Back Yard" (NIMBY) facilities in the city is inevitable. To resolve NIMBY conflict, it is important to know people's NIMBY risk acceptability for these facilities. A questionnaire survey was used among Chinese and Japanese college students to identify NIMBY risk acceptability. LISREL was used to construct a structural equation model to analyze the difference in NIMBY risk acceptability between the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Studies have found that people tend to oppose LULUs because of their potentially hazardous activities and materials and the perceived risks associated with them; inspired by these findings, this study posited that trust in the safety of the management of disaster waste is a positive determinant of one's willingness to accept waste (H1 in Table ) because that would reduce the perceived risks associated with the probability of an undesirable event. This hypothesis was also in line with the findings that perceived safety was a significant determinant of public acceptance of the construction of a nuclear power plant in South Korea, as was trust in the technical competency of those who oversaw safety at a nuclear power plant in the United States .…”
Section: Hypothesesmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies have found that people tend to oppose LULUs because of their potentially hazardous activities and materials and the perceived risks associated with them; inspired by these findings, this study posited that trust in the safety of the management of disaster waste is a positive determinant of one's willingness to accept waste (H1 in Table ) because that would reduce the perceived risks associated with the probability of an undesirable event. This hypothesis was also in line with the findings that perceived safety was a significant determinant of public acceptance of the construction of a nuclear power plant in South Korea, as was trust in the technical competency of those who oversaw safety at a nuclear power plant in the United States .…”
Section: Hypothesesmentioning
confidence: 98%
“…Risk perception is culturally and socially determined and is influenced by the saliency of the issue . Given Japan's experience with nuclear bombings, the dread of radiation is understandable there, where “the horrifying images” of atomic power are overwhelming and where “it took a post‐war publicity campaign by the US government, in collaboration with Japanese officials and businessmen, to sell the Japanese public on the peaceful use of atomic energy.” A representative survey conducted by the Cabinet Office in 2009 revealed signs of improved public perception: 53.9% of the public were feeling anxious about the nuclear power plant—a drop from 65.9% in 2005— whereas 59.6% supported the promotion of nuclear energy, an increase from 55.1% in 2005 .…”
Section: Hypothesesmentioning
confidence: 99%
“…Following this critical approach to the conventional view, the siting literature has identified a number of environmental, social, and psychological factors that are likely to foster a negative response to unwanted facilities: (a) the aesthetic impact of the facility itself, and relationships with out-siders (Hagget, 2011); (b) the type of facility, and the clarity of choice (Esaiasson, 2014); values concerning environmental injustice and the fairness of the siting process (Wolsink & Devillee, 2009); (d) unwanted consequences, such as health and material concerns, and detrimental changes in quality of life (Schively, 2007); (e) perception of risks associated to the facility (Hunter & Leyden, 1995;Pol, Di Masso, Castrechini, Bonet, & Vidal, 2006;Wu, Zhai, Li, Ren & Tsuchida, 2014); and (f) trust in the authorities, decision makers, and development organizations (Groothuis & Miller, 2005;Gross, 2007). Most important for this study, along with the studies that addressed specific and discrete aspects of each project, a second strand of research has focused on two other environmental psychological issues.…”
Section: This Interpretation Led the First Researchers Into This Topimentioning
confidence: 99%
“…It has been found that psychiatric rehabilitation services have been categorized as one of the “not in my back yard” (NIMBY) facilities. Therefore, people living nearby tend to avoid these facilities in their area [ 41 ]. The effect of ostracization from community residents reflects the fact that they still have concerns about mental illness [ 42 ].…”
Section: Introductionmentioning
confidence: 99%